PENGARUH PENAMBAHAN LIMBAH BOTOL KACA TERHADAP DAYA SERAP AIR DAN UJI KUAT TEKAN BATU BATA MERAH - Al Havis Ari Winata; Ishak Ishak; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The background of the author doing this research is to improve the construction of houses at this time. This study aims to determine the benefits and strength of ordinary red bricks without mixing with red bricks that have been mixed with glass bottle waste and also to determine the value of water absorption and the value of the compressive strength of red bricks that have been added to a mixture of glass bottle waste. The research that the author did here made samples of bricks and tested water absorption, compressive strength, and made samples in a brick factory located in Manggis Village, Mandiangin Koto Selayan District, Bukittinggi City, as well as testing samples in the laboratory of the Faculty of Engineering, Muhammadiyah University, West Sumatra. In collecting the data needed by the author is a direct survey of the spaciousness and testing the water absorption and compressive strength in the laboratory. In the mixing method, the percentages are 0%, 2%, 4%, 6% and 8%. From the results of research conducted adding glass bottle powder with mixed percentages of 2%, 4%, 6% and 8% can affect the value of water absorption and compressive strength of red bricks, a mixture of 4% has low compressive strength and sufficient water absorption. high so that it is not possible to use in the construction sector. However, the 8% mixture has a higher number than other mixtures and is close to a 0% mixture, a mixture of 8% and 6% red bricks can still be used in the construction sector because the results of water absorption and compressive strength are still close to SNI 15-2094-200 . Keywords: Red brick, Glass Powder, water absorption, compressive strength